Time Scale of Chloride-Induced Corrosion on Circular Section RC Linked Accelerated Test to Natural Corrosion - Yue Zhang; Fangyan Lan; Mi Zhou; Ke Wang (Advances in Civil Engineering)
The time scale in accelerated decay is essential for studying the durability of reinforced concrete (RC) structures exposed to the chloride corrosion environment. An accelerated corrosion test (ACT) was carried out on RC specimens were conducted under different chloride concentrations and applied voltages, with the information of steel measured. A novel prediction model of the complete corrosion process is proposed to evaluate the time correlation between accelerated decay and natural corrosion. The corrosion process of RC is divided into two stages: corrosion initial stage and corrosion stage of reinforcement. For the first stage, the coefficient of circular section members is presented. For the second stage, the accelerated factor of the test for the natural environment is proposed based on the Arrhenius-type and Faraday’s law. It is calculated by making regressions among some values of parameters, while moving to natural corrosion are extrapolating. The accelerating effect of applied voltages increases in the low-chloride environment, which is better than that in the high-chloride environment. This study provides calibration of the time scale for laboratory tests to analyze the performance of RC structures after corrosion.